(untitled) (Experimental biology, 2020)
Investigation of nutrition and nutritional relationships of fish in the Northern Caspian is needed because this part of the water body is a feeding site for many fish species. The nutritional material was selected in the course of conducting comprehensive marine research in the Kazakhstan Caspian Sea waters, in the summer and autumn of 2018. A feeding research of such predatory fish as pike perch, asp, and sabrefish, as well asbream, roach, crucian carp, and golden mullet obtained from trawl catches, made it possible to trace the overall productivity formation of the reservoir and determine the reservoir water content. The researched fish had gastrointestinal tracts sufficiently filled with food. Fish with empty stomachs were rarely seen which indicates good nutrition and active consumption of food. It was revealed also that crustaceans, mollusks, and worms constituted the basis of the food intake of the fish of the benthophagous; while predatory species fed on the advanced fry. This suggests food plasticity and selectivity of fish. Also, benthophagous fish can eat a variety of food, and thus not create competition for each other in the diet. The lowest indices of gastrointestinal filling were in predatory fish species. The basis of the food lump in all analyzed fish was digested food. It can be noted that the fish caught on the digestive organs in the fall had fatty layers indicating that the fish were fed and did not experience a deficit in the food objects. According to the results of the research, the seasonal species diversity of feed objects in the north - eastern part of the Caspian Sea was also established. Keywords: Caspian Sea, food, foraminifera, worms, crustaceans, mollusks.